Answer:
x=−2
Step-by-step explanation: Step 1: Simplify both sides of the equation.
3(x−5)−3=5(x−2)+2x
(3)(x)+(3)(−5)+−3=(5)(x)+(5)(−2)+2x(Distribute)
3x+−15+−3=5x+−10+2x
(3x)+(−15+−3)=(5x+2x)+(−10)(Combine Like Terms)
3x+−18=7x+−10
3x−18=7x−10
Step 2: Subtract 7x from both sides.
3x−18−7x=7x−10−7x
−4x−18=−10
Step 3: Add 18 to both sides.
−4x−18+18=−10+18
−4x=8
Step 4: Divide both sides by -4.
−4x
−4
=
8
−4
x=−2
Answer:
The equation of the line would be y + 4 = -1/8(x + 6)
Step-by-step explanation:
To find the point-slope form of the line, start by finding the slope. You can do this using the slope formula below along with the two points.
m(slope) = (y2 - y1)/(x2 - x1)
m = (-4 - -5)/(-6 - 2)
m = 1/-8
m = -1/8
Now that we have the slope, we can use that along with one of the points in the base form of point-slope.
y - y1 = m(x - x1)
y + 4 = -1/8(x + 6)
Combine the like terms:
3 - 12t + 8t = 3 - 4t
simplified answer is
-4t + 3
Answer:
x = 6 ; Rewritten: 2x-3y-12=0 ; y=-4
Step-by-step explanation:
2x-3 multiply 0=12
x=6 ( that's the function)
Rewritten steps: 2x-3y=12 then move constant to the left by adding its opposite to both sides which gives you 2x-3y-12=12-12. After the sum of two opposites equals 0 which is 2x-3y-12=0
Y Intercept :
2x-3y=12 and to find y intercept, sub x = 0 ; to 2 multiply 0 -3y=12 and then you solve for the equation which is your answer.